2011
DOI: 10.4103/0971-4065.83735
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nicotinamide in the management of hyperphosphatemia in patients on hemodialysis

Abstract: Hyperphosphatemia is an important modifiable risk factor for death and cardiovascular events in patients on hemodialysis (HD). As nicotinamide has been shown as an inhibitor of sodium–dependent phosphate co–transport in rat renal tubule and small intestine, we examined whether nicotinamide reduces hyperphosphatemia in patients undergoing HD. The study was conducted in 30 end-stage renal disease (ESRD) patients [20 (66.7%) males and 10 (33.3%) females; mean age 54 ± 14.9 years] undergoing twice/thrice weekly HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Additionally, some cases of early termination can be attributed to chemotherapy-induced alterations of sweat gland functions (hyperhidrosis) and the olfactory sense (dysosmia). The present study data and published data raise no safety concerns for clinical use 47–49. Furthermore, niacinamide has been used systemically as a perfusion enhancer for palliative care in patients with breast cancer due to its relaxant effects on vascular smooth muscle cells 50,51…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, some cases of early termination can be attributed to chemotherapy-induced alterations of sweat gland functions (hyperhidrosis) and the olfactory sense (dysosmia). The present study data and published data raise no safety concerns for clinical use 47–49. Furthermore, niacinamide has been used systemically as a perfusion enhancer for palliative care in patients with breast cancer due to its relaxant effects on vascular smooth muscle cells 50,51…”
Section: Discussionmentioning
confidence: 57%
“…The present study data and published data raise no safety concerns for clinical use. [47][48][49] Furthermore, niacinamide has been used systemically as a perfusion enhancer for palliative care in patients with breast cancer due to its relaxant effects on vascular smooth muscle cells. The results of this study suggest that cytostatic cutaneous symptoms among other health problems have a negative impact on quality of life for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…NAM is now known to inhibit sodium/phosphorous transport in both renal and intestinal brush borders, stimulating interest in its use for phosphorus reduction among patients with ESRD. As a result, there is solid experimental evidence that NAM decreases phosphorus levels in HD patients [12][13][14][15][16][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Our results correlate with those reported by Cheng et al [19] and Young et al [20] which demonstrated that NAM lowers serum phosphorus levels in maintenance HD patients when co-administered with other phosphate binders. On the other hand, Takahashi et al [16], Sampathkumar et al [21] and Vasantha et al [22] reported that NAM reduces serum phosphorus even when traditional binding agents were withheld.…”
Section: Discussionmentioning
confidence: 99%